Investigating the impact of IKZF1 SNPs rs4132601 and rs11978267 on acute lymphoblastic leukemia: a comprehensive meta-analysis - Sheena Mariam Thomas; Jethendra Kumar Muruganantham; Praveen Kumar Chandra Sekar; B. K. Iyshwarya; Ramakrishnan Veerabathiran (Journal of the Egyptian National Cancer Institute)
Abstract Objective This meta-analysis investigates the association between acute lymphoblastic leukemia (ALL) susceptibility and IKZF1 gene SNPs. Methods Utilizing EMBASE, PubMed, and other databases, the study evaluated methodological quality through the Newcastle–Ottawa Scale (NOS) scoring and Hardy–Weinberg Equilibrium (HWE) value. The present meta-analysis used Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. Review Manager 5.4 software was employed for data analysis, emphasizing genetic variants' significance (p < 0.05). Visualizations were achieved using funnel and Circos plots. Results A significant association was found between rs4132601 and ALL across genetic models, contrasting with the non-significant correlation for rs11978267. The findings underscore the complex interplay of genetic factors in ALL susceptibility, particularly related to IKZF1 SNPs. Ethnicity emphasizes the importance of diverse population considerations. Conclusion This meta-analysis highlights the significance of rs4132601 in ALL's genetic foundation, suggesting potential advancements in diagnostics. The lack of correlation for rs11978267 highlights the complexity of its genetic association. Future studies should prioritize larger, diverse samples for a comprehensive understanding and improved strategies for ALL diagnoses and treatments.